Strategi Komunikasi Dinas Pariwisata Provinsi Nusa Tenggara Barat dalam Meningkatkan Kunjungan Wisatawan Lombok Sumbawa tahun 2016 – 2017 - Diana Juwita; Siti Chotijah; Arifudin Sahidu (JCommsci - Journal Of Media and Communication Science, 2018)
Lombok Sumbawa has experienced rapid tourist growth in the last 5 years. The achievements obtained by Lombok Sumbawa in the increase of tourist visits in 2016 and 2017 are certainly the achievements made by the NTB Provincial Tourism Office on the programs implemented. This research is important because tourism in NTB is a sector that plays an important role in economic growth in NTB. The purpose of this study was to find out the Communication Strategy of the NTB Province Tourism Office in Increasing Visits of Lombok Sumbawa Tourists in 2016 - 2017. This study used a descriptive method. The research was carried out at the NTB Provincial Tourism Office, with the main information sources being the Head of Market Analysis of the NTB Provincial Tourism Office. The results showed that the NTB Provincial Tourism Office implemented a communication strategy in increasing Lombok Sumbawa tourism visits in 2016 - 2017. The communication strategy carried out by the NTB Provincial Tourism Office was (1) Collaboration on Penta Helix Synergy, (2) Events, and (3) Promotion. This communication strategy is able to increase tourists visiting Lombok Sumbawa in 2016 - 2017, which is 3,094,437 (1,690,109 domestic tourists, 1,404,328 foreign tourists) in 2016, and 3,508,903 (2,078,654 domestic tourists, and 1,430,249 foreign tourists in 2017.